The Effect of Tax Audit, Tax Collection, and Taxpayer Compliance Supervision on Increasing Tax Revenue at KPP Pratama Makassar Utara - K. Kamaruddin; Ahmad Faisal; Muhammad Rizal Agustam (Golden Ratio of Taxation Studies, 2022)
This study aims to determine the effect of tax audits, tax collections, and monitoring of taxpayer compliance on increasing tax revenues. The data collection method used a questionnaire. The sampling technique was based on the non-probability sampling method with a purposive sampling technique on 56 respondents at the Pratama Tax Service Office in KPP Makassar Utara who were in the Audit section including tax examiners, billing sections, and supervision and consulting sections 2, 3, and 4. Research This research uses quantitative analysis using multiple regression methods and is tested by data quality test, classic assumption test, and hypothesis test using IBM SPSS statistics version 22. The results showed that partially and simultaneously tax audits, tax collection, and monitoring of taxpayer compliance proved to have a significant positive effect on increasing tax revenues.